Peningkatan Kompetensi Guru dalam Menyusun Proposal Penelitian Tindakan Kelas (PTK) Melalui Workshop - Isa, Mochammad (Islamic Education, 2022)
The problem of delays in teacher promotion is said to lead to low teacher interest, understanding, and ability to write papers. This is proven by the finding of teachers who cannot apply for a promotion because they do not have written papers as a requirement for promotion. This study aims to improve teacher competence in writing school action research reports (PTS) through workshops which are carried out in stages and continuously. School Action Research (PTS) was carried out in assisted schools in Sidoarjo district and the problem studied was Efforts to Increase Teacher Competence in Preparing PTK Proposals through Workshops with direct and continuous guidance and coaching. In implementing PTS, the procedure is to carry out a workshop with two cycles for teachers in two target schools and provide technical guidance on the preparation of PTK proposals. The results showed that the teacher's ability in activities, interests, and the results of preparing proposals after the workshop activities had increased.